Spatio-Temporal Changes in the Grass Land Cover of Manas National Park - Pavan Kumar, K. S. P. V.; Vijaya Lakshmi, T.; Goswami, Abhijit (Indian Forester, 2023)
Manas National Park, a UNESCO natural world heritage site, located in the foothills of the Eastern Himalayan range has a rich diversity of flora and fauna. Manas National Park (MNP) is facing natural as well as anthropogenic challenges. The present study is carried out by using geospatial technology as an attempt to analyse the land use and land cover change over a period from 1973 till 2022. The geospatial technology is being used as a timely and cost-effective way to carry the study as the site remained inaccessible during the long period of insurgency and no adequate database is readily available. Results indicated that there has been significant decrease in the grassland areas, rise in encroachment and changes in the river course inside the park.